Blasticidin S inhibits mammalian translation and enhances production of protein encoded by nonsense mRNA - Powers, Kyle T.; Stevenson-Jones, Flint; Yadav, Sathish K N; Amthor, Beate; Bufton, Joshua C; Borucu, Ufuk; Shen, Dakang; Becker, Jonas Philipp; Lavysh, Daria; Hentze, Matthias W.; Kulozik, Andreas; Neu-Yilik, Gabriele; et al. (Nucleic acids research, 2021)
Deciphering translation is of paramount importance for the understanding of many diseases, and antibiotics played a pivotal role in this endeavour. Blasticidin S (BlaS) targets translation by binding to the peptidyl transferase center of the large ribosomal subunit. Using biochemical, structural and cellular approaches, we show here that BlaS inhibits both translation elongation and termination in Mammalia. Bound to mammalian terminating ribosomes, BlaS distorts the 3′CCA tail of the P-site tRNA to a larger extent than previously reported for bacterial ribosomes, thus delaying both, peptide bond formation and peptidyl-tRNA hydrolysis. While BlaS does not inhibit stop codon recognition by the eukaryotic release factor 1 (eRF1), it interferes with eRF1’s accommodation into the peptidyl transferase center and subsequent peptide release. In human cells, BlaS inhibits nonsense-mediated mRNA decay and, at subinhibitory concentrations, modulates translation dynamics at premature termination codons leading to enhanced protein production.